Performance of Brinjal Genotypes for Growth, Yield and Quality Characters under Terai Zone of West Bengal - Kumar, Raushan; Kumar, Prince; Das, Satadal; Basfore, Shibnath; Kumar, Raj; Sikder, Subhmoy (International Journal of Bio-resource and Stress Management, 2025)
The present field experiment was conducted during August, 2023–June, 2024 at UBKV, Pundibari, West Bengal, India to evaluate 25 indigenous brinjal (Solanum melongena L.) genotypes for growth, yield and quality characteristics. The trial, laid out in Randomized Block Design with three replications and observation were recorded on different growth, yield and quality attributes of brinjal. The results of experiment revealed significant genotypic variation for all traits, highlighting the scope for selection. Genotype 2022/BRLVAR-8 excelled in plant height (103.06 cm) and number of fruits plant-1 (25.78), while 2022/BRLVAR-3 recorded maximum branches (5.49). Early flowering was noted in 2022/BRLVAR-6 (60.56 days) and genotype 2022/BRLVAR-5 had the longest fruit lenth (18.31 cm), and 2022/BRR VAR-15 had the maximum fruit width (8.94 cm) and fruit weight (214.60 g). Maximum yield plant-1 was observed in 2022/BRR VAR-5 (2.41 kg), while 2022/BRR VAR-2 gave the highest total yield plot-1 (41.57 kg). Genotype 2022/BRR VAR-5 also recorded the highest projected yield (30.00 t ha-1). For quality traits, 2022/BRLVAR-5 had the highest TSS (6.65°Brix), 2022/BRLVAR-2 had highest ascorbic acid (12.47 mg 100 g-1), 2022/BRR VAR-2 had the highest anthocyanin (80.52 mg 100 g-1), and 2022/BRLVAR-6 had the highest phenol content (2.24 mg 100 g-1). The genotypes 2022/BRR VAR-5, 2022/BRR VAR-4 and 2022/BRLVAR-5 emerged as promising genotypes for yield and quality traits under Terai conditions of West Bengal. These genotypes should be advanced for multilocation trials and utilized in future breeding programs to develop high-yielding, nutrient-rich brinjal cultivars adaptable to Eastern India.